Strengthening the Capacity to Adapt to Climate Change among Farmers in a Banana Center in Java, Indonesia - Wibowo, Agung; Lestari, Eny; Rahayu, Paramita (Komunitas, 2023)
Climate change causes basic problems in the lives of farmers in a banana center, such as a decrease in the quality and quantity of bananas. The various impacts of climate change will not cause food insecurity if the community has an adequate adaptive capacity. The purpose of this study is to analyze the capacity of farmers in a banana center to adapt to a change in the quality and quantity of bananas due to climate change. In-depth interviews, observation and focus group discussions were used to collect data. The unit of analysis is at the individual level in society. The data analysis was carried out through the stages of data reduction, data presentation, and drawing a conclusion. The results show that the development of community capacity to maintain the quality and quantity of bananas is carried out by strengthening the capacity of individuals, groups, and institutions that play an important role in adapting to climate change. This has an impact on the collective action of the community to maintain the sustainability of the banana center.